Study on Remission in Depression and Associated Factors at Different Assessment Times in Primary Care in Chile - Veronica Vitriol; Alfredo Cancino; Carlos Serrano; Soledad Ballesteros; Soledad Potthoff (Highlights on Medicine and Medical Research Vol. 6, 2021)
Objective: To determine the factors associated with remission at 3, 6, 9 and 12 months among depressive adult patients in primary care (PHC) in Chile. Methods: This is a one-year naturalistic study that followed 297 patients admitted for treatment for depression in eight primary care clinics in Chile. Initially, patients were evaluated using: The international mini-neuropsychiatric interview (MINI), a screening for childhood trauma events (CTEs), the Life Experiences Survey and a partner violence scale. The Hamilton Depression Scale (HDRS) was used to follow the patients during the observation time. Association between the factors studied and the primary outcome remission (HDRS \(≤\) 7) were assessed using a dichotomous logistic regression and a multivariate Poisson regression. The significance level was 0.05. Results: Remission (HDRS \(≤\) 7) ranged between 36.7% at 3 months and 53.9% at 12 months. Factors that predicted poor remission during the observation- time were: CTEs (Wald X2 = 4,88 Exp B=0.94 CI 0.90- 0.92 p=0.27); psychiatric comorbidities (Wald X2 = 10.73 Exp B=0.9 CI 0.85- 0.96 p=0.01); suicidal tendencies (Wald X2 = 4,66 Exp B=0.88 CI 0.79- 0.98 p=0.031) prior treatment depression (Wald X2 = 4.50 Exp B=0.81 CI 0.68- 0.85 p=0.03). Discussion: Almost 50% of this sample failed remission in depression at 12 months. Psychiatric comorbidities and CTEs are factors that should be considered for a poor outcome in depressive Chilean patients. These factors need more recognition and a better approach in PHC. The findings of this study indicate that other strategies aimed at improving the recognition of these clinical and psychosocial factors in depressed patients should be incorporated in PHC.